For a media Semiology - Jost, François (2012)
This paper discuss the complex relations adopted by Semiology and media theory, to propose a televisual communication oriented semiotics, capable to embrace the specificities of this kind of media process. Thus, after to point the inadequacy of the elements enforcement of a immanent Semiology, or apllied to cinema, to the television analysis, it endorses the notion of gender promise as a replacement to the notion of contract or pact, as subjacent to the media communication.